Improving Students' Interest in Reading at SDN Gembira Sikka Regency through the Reading Corner: Peningkatan Minat Baca Peserta Didik di SDN Gembira Kabupaten Sikka melalui Pojok Baca - Maria Filestina Hiko; Yohanes Bare; Yohanes Nong Bunga; Sukarman Hadi Jaya Putra (Yayasan Ahmar Cendekia Indonesia, 2022)
Community service activities at SD Negeri Gembira, Sikka Regency are to create a reading corner in the library. The purpose of creating a reading corner is to increase students' interest and motivation to read, encourage better library management, and help students to be able to take advantage of free time by reading. The activity of making a reading corner is an effort made as an answer to the problems found in the learning process in the classroom, namely that there are still students who have not been able to manage smoothly even though they have been in class VI. The use of the reading corner is made to target specifically for class VI students but does not close the opportunity to all students of SD Negeri Gembira. A series of PkM activities have been carried out from August to November 2022. All components at SD Negeri Gembira strongly support the creation of a reading corner. Learners have shown progress in learning especially reading proficiency.